Growth, flowering and presentability of potted azaleas as influenced by pot size and cultivars - DILTA, B S; THAPA, SUMAN; GUPTA, Y C; SHARMA, B P; NEGI, NARENDER; KAUSHAL, SAPNA (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was carried out at the experimental farm of the Department of Floriculture and Landscape Architecture, Dr Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan (HP) during (2013- 14) to find out most suitable cultivar and pot size for producing best quality and most presentable potted azaleas. The experiment was laid out in a Factorial Completely Randomized Block Design having 45 treatment combinations, viz. fifteen cultivars (John Herrens, Winter Hawk, White Rosebud, Boy-O-Boy, Summer Time, Pink Tama, Red Tomahawk, Shanghai Baby, Super Red, Nightingale, Empress, White Bouquet, Lady Love, Anniversary Joy and Royalty) and three pot sizes (25 , 20 cm and 15 cm diameter) respectively. Results revealed that among the various cultivars used ‘White Bouquet’ recorded maximum values in terms of most of desirable characters viz., number of shoots per plant (22.77), plant spread (45.18 cm), number of flowers per plant (27.39), number of flowers per plant open at a time (19.34) and pot presentability score (84.33) whereas among the pot sizes, 25 cm diameter pots exhibited maximum plant height (32.95 cm), maximum shoots per plant (17.35), plant spread (32.06 cm), number of flowers per plant (18.04), flower diameter (7.31 cm), number of flowers opened at a time (13.50) and pot presentability score (74.71). The interaction effects of cultivars and pot sizes indicated that cv. ‘White Bouquet’ gave better performance w.r.t. various growth, flowering and presentibility attributes of potted azaleas especially when grown in 25 cm diameter pots.